The Construction of Social Identity Through Digital Games Mobile Legends Bang Bang - Hafidha Adila Rahma; Yusri Fajar (Universitas Dian Nuswantoro, 2022)
SIT (Social Identity Theory) has been extensively used to study group identity and its implications in a variety of contexts, but SIT's relevance has gotten less attention in digital gaming. The article examines how the digital game Mobile Legends Bang Bang constructs social identity based on the observation outcomes attributed to gaming identity through the phenomenon of digital gaming. A qualitative approach guided the data analysis in this research. Moreover, this study gathers data using online questionnaires and interviews with five participants of Mobile Legends Bang Bang's players. The analysis indicates that Mobile Legends Bang-Bang has contributed to the construction of social identity, which is associated with aspects of existing social networks and virtual communities while generating new forms of cultural activity.Keywords: digital games, gamer, mobile legends, social identity, virtual communityAbstrak. SIT (Teori Identitas Sosial) telah banyak digunakan untuk mempelajari identitas kelompok dan implikasinya dalam berbagai konteks, tetapi relevansi SIT kurang mendapat perhatian dalam permainan digital. Artikel ini mengkaji bagaimana game digital Mobile Legends Bang Bang mengkonstruksi identitas sosial berdasarkan hasil observasi yang dikaitkan dengan identitas game melalui fenomena game digital. Analisis data dalam penelitian ini berpedoman pada pendekatan kualitatif. Selain itu, penelitian ini mengumpulkan data melalui aktivitas virtual dan mewawancarai lima partisipan dari pemain Mobile Legends Bang Bang. Analisis menunjukkan bahwa Mobile legends Bang Bang secara umum telah menemukan identifikasi positif dalam mengkonstruksi identitas sosial, yang dikaitkan dengan aspek jaringan sosial yang ada, dan komunitas virtual sekaligus juga menghasilkan bentuk-bentuk aktivitas budaya baru.Kata kunci: game digital, pemain permainan, mobile legends, identitas sosial, komunitas virtual